Sustainable Knowledge - Frodeman, R. author. aut Link
VI, 127 p.
Keywords: Sustainable Knowledge rethinks the nature of interdisciplinary research and the place of philosophy and the humanities in society and offers a new account of what is at stake in talk about 'interdisciplinarity'.